The Feasibility Study of Light Vehicle Engineering Electrical Practice Facilities and Infrastructure at Vocational Education School - Ahmad Arif; Ambiyar Ambiyar; Nurhasan Syah; R. Chandra; Wawan Purwanto; Nuzul Hidayat; Muhammad Yanda (Universitas Muhammadiyah Enrekang, 2022)
The completeness and feasibility of infrastructure in the world of education is something that must be considered and fulfilled. This has an impact on learning outcomes and students' abilities. This study aims to determine the feasibility of facilities and infrastructure in the light vehicle engineering electrical practice workshop at Padang 1 State Vocational Education School. This research uses descriptive analysis method. Research data obtained from interviews, documentation, and direct observation at school. The data on facilities and infrastructure that has been obtained is then compared with the standards of facilities and infrastructure listed in the Regulation of the Minister of Education of the Republic of Indonesia number 40 of 2008 and the National Education Standards Agency number 1049-P2 of 2010/2011. The results showed that the level of feasibility of the facilities and infrastructure for the electrical practice light vehicle engineering Padang 1 State Vocational Education School was 56.42% and 53.32% which were included in the feasible category. Existing electrical practice learning facilities and infrastructure can still be used and schools are expected to improve their quality.